2003
DOI: 10.1111/j.1756-1051.2003.tb00419.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and development of secretory structures in Hypericum perforatum and H. richeri

Abstract: 2005. Morphology and development of secretory structures in Hypericum perforatum and H. richeri. -Nord. J. Bot. 23: 453-461. Copenhagen. ISSN 0107-055X.Secretory organs are a specialised anatomical feature of plants, these tissues function in the production andor storage of specific chemical substances, which often have pharmacological properties. The genus Hypericum is characterised by the presence of specialised secretory structures such as black nodules, translucent glands and secretory canals. The presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Hence, compared to the other classes of compounds, EO from in vitro shoots of Hypericum species are less complex than those from in vivo plants (Guedes et al 2003, Guedes 2009), probably due to the undifferentiated secretory structures of in vitro shoot cultures. In Hypericum plants, EO were shown to be accumulated in both translucent glands and type B cannals structures (Ciccarelli et al 2001;Maffi et al 2005 . In the EO of in vitro shoots of this species, the authors found also a narrow range of compounds and a pattern of metabolites that discloses a very early part of the biosynthetic pathway.…”
Section: Biotechnology In Hypericum Essential Oil Improvementmentioning
confidence: 99%
“…Hence, compared to the other classes of compounds, EO from in vitro shoots of Hypericum species are less complex than those from in vivo plants (Guedes et al 2003, Guedes 2009), probably due to the undifferentiated secretory structures of in vitro shoot cultures. In Hypericum plants, EO were shown to be accumulated in both translucent glands and type B cannals structures (Ciccarelli et al 2001;Maffi et al 2005 . In the EO of in vitro shoots of this species, the authors found also a narrow range of compounds and a pattern of metabolites that discloses a very early part of the biosynthetic pathway.…”
Section: Biotechnology In Hypericum Essential Oil Improvementmentioning
confidence: 99%
“…It has generally been accepted that hypericin primarily accumulates in the dark glands in both leaves and flowers (Mathis and Ourisson, 1963;Robson, 1981;Ciccarelli et al, 2001a;Maffi et al, 2005) but only recently was it demonstrated that there exists a positive correlation between the size and number of dark glands and the overall content of hypericin in the plant organ (Zobayed et al, 2006). In Hypericum elodes hypericin has been shown to accumulate in the 'red glands' peripherally on sepals; removal of these red glands indicated that hyperforin accumulated elsewhere (Piovan et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was demonstrated that various compounds isolated from Hypericum exhibited cytotoxicity against cancer cell lines, showed antibacterial (Feyzioglu et al 2013) and anthelmintic activities as well as anti-HIV activity in infected MT-4 cells (Fobofou et al 2015). Hypericin accumulates in specialized organs called dark glands (Mathis and Ourisson 1963;Robson 1981;Southwell and Campbell 1991;Fornasiero et al 1998;Maffi et al 2005;Zobayed et al 2006;Kusari et al 2015;Rizzo et al 2019), whereas hyperforin accumulates in other structures called translucent glands (Soelberg et al 2007). The dark glands are found in: margin of petals and leaves, sepals, pistils, anther tips and sometimes on stems of the plants but not on roots (Rizzo et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Agrobacterium-mediated transformation in Hypericum has proven to be very difficult (Mathis and Ourisson 1963;Southwell and Campbell 1991;Fornasiero et al 1998;Maffi et al 2005;Zobayed et al 2006;Hou et al 2016). Increased production of xanthone and accumulation of active biological compounds were detected upon co-cultivation with Agrobacterium (Franklin et al 2009) in Hypericum suspension cultures.…”
Section: Introductionmentioning
confidence: 99%